EEG Correlates of Self-Managed Neurofeedback Treatment of Central Neuropathic Pain in Chronic Spinal Cord Injury - Vučković, Aleksandra; Altaleb, Manaf Kadum Hussein; Fraser, Matthew; McGeady, Ciarán; Purcell, Mariel (Frontiers in Neuroscience, 2019)
Background: Neurofeedback (NFB) is a neuromodulatory technique that enables voluntary modulation of brain activity in order to treat neurological condition, such as central neuropathic pain (CNP). A distinctive feature of this technique is that it actively involves participants in the therapy. In this feasibility study, we present results of participant self-managed NFB treatment of CNP. Methods: Fifteen chronic spinal cord injured (SCI) participants (13M, 2F), with chronic CNP equal or greater than 4 on the Visual Numeric Scale, took part in the study. After initial training in hospital (up to 4 sessions), they practiced NF at home, on average 2-3 times a week, over a period of several weeks (min 4, max 20). The NFB protocol consisted of upregulating the alpha (9-12 Hz) and downregulating the theta (4-8 Hz) and the higher beta band (20-30 Hz) power from electrode location C4, for 30 min. The output measures were pain before and after NFB, EEG before and during NFB and pain questionnaires. We analysed EEG results and show NFB strategies based on the Power Spectrum Density of each single participant. Results: Twelve participants achieved statistically significant reduction in pain and in eight participants this reduction was clinically significant (larger than 30%). The most successfully regulated frequency band during NFB was alpha. However, most participants upregulated their individual alpha band, that had an average dominant frequency at p=7.6±0.8 Hz (median 8 Hz) that is lower than the average of the general population, which is around 10 Hz. Ten out of fifteen participants significantly upregulated their individual alpha power (p±2Hz) as compared to 4 participants who upregulated the power in the fixed alpha band (8-12 Hz). Eight out of the twelve participants who achieved a significant reduction of pain, significantly upregulated their individual alpha band power. There was a significantly larger increase in alpha power (p<0.0001) and decrease of theta power (p<0.04) in participant specific rather than in fixed frequency bands. Conclusion: Neurofeedback is a neuromodulatory technique that gives participants control over their pain and can be self-administered at home. Regulation of individual frequency band was related to a significant reduction in pain.